2020
DOI: 10.1111/1756-185x.13837
|View full text |Cite
|
Sign up to set email alerts
|

Distinct HLA and non‐HLA associations in different subtypes of ANCA‐associated vasculitides in North India

Abstract: Aim: Antineutrophil cytoplasmic antibody-associated vasculitis (AAV) is an autoimmune disease characterized by necrotizing small vessel vasculitis that can affect various organs and present multiple symptoms. Susceptibility to AAV is multifactorial and most likely caused by an amalgamation of genetic and environmental factors. The aim of the present study was to explore the distribution of human leukocyte antigen (HLA)-DRB1/DQB1, protein tyrosine phosphatase non-receptor type 22 (PTPN22) and cytotoxic T-Lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Another study demonstrated that the CTLA-4-318 SNP was associated with GPA susceptibility [27]. The GG genotype of CTLA-4 + 49A/G was found to be correlated with AAV (PR3-AAV and GPA) in an Indian cohort [18]. The A allele of rs3087243 CTLA has been found to be a protective factor against AAV [28].…”
Section: Co-stimulatory Molecules and Signaling Regulatorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study demonstrated that the CTLA-4-318 SNP was associated with GPA susceptibility [27]. The GG genotype of CTLA-4 + 49A/G was found to be correlated with AAV (PR3-AAV and GPA) in an Indian cohort [18]. The A allele of rs3087243 CTLA has been found to be a protective factor against AAV [28].…”
Section: Co-stimulatory Molecules and Signaling Regulatorsmentioning
confidence: 97%
“…Also, the HLA-DRB4 alleles were found to be related to symptoms of vasculitis in German patients [17]. In a recent study, the DRB1*03 and DQB1*02 alleles were associated with confirmed in proteinase 3 (PR3)-AAV patients, whereas the DRB1*10, DRB1*14, and DQB1*05 were found to be protective alleles in AAV [18].…”
Section: Open Accessmentioning
confidence: 98%
“…Three studies were found eligible for the meta-analysis and were evaluated. 8,15,33 A allele of rs2476601 was identified to provide borderline risk (Meta-OR = 1.17 [0.55-2.48]; P = .69) with nonsignificant association (Figure 2H).…”
Section: Ptpn22mentioning
confidence: 99%
“…14 Although not consistently observed in candidate gene studies, the significant association of −1858 C/T, rs2476601 with GPA/MPA was reported in Caucasians but was not replicated among Indians. 6,15 An association of PRTN3 promoter polymorphisms rs231775-G and A564G was observed in Germans, which was not replicated among European Americans. 16,17 These genetic variants from CTLA4, PRTN3, SERPINA1 and PTPN22 have been studied in distinctly different ethnic populations and association heterogeneity was observed.…”
Section: Introductionmentioning
confidence: 98%
“…With regards to the HLA region, the alleles DPA1, DPB1 * 04:01, DPB1 * 04:02, DPB1 * 23:01, DQB1 * 02 , and DRB1 * 03 were associated with the development of PR3-ANCAs, whereas DQA1 * 03:02, DQB1 * 03:03 , and DRB1 * 09:01 were associated with the MPO-ANCAs ( 38 , 53 ). These risk factors were identified based on previous association studies ( 35 , 37 , 38 , 53 , 54 ).…”
Section: Genetic Variants and Their Association With Immunopathogenesis In Vasculitismentioning
confidence: 99%